EVALUATION OF STYLOID PROCESS MORPHOLOGY AND CALCIFICATION TYPES IN BOTH GENDERS WITH DIFFERENT AGES AND DENTAL STATUS - Güldane MAĞAT; Sevgi ÖZCAN (Istanbul University, 2017)
Purpose: The purpose of this study was to investigate the morphology and calcification pattern of the styloid process (SP) and to determine their relations with subjects' age, gender, and dental status. Materials and Methods: 910 panoramic radiographs were stratified by age, dental status and gender. The distance between the points where SP leaves the tympanic plate of the temporal bone and the bony tip of SP was measured. Calcification patterns were classified as : (A) Region 1, tympanohyal alone (B) Region 2, stylohyal alone (C) Region 1 and 2, separate (D) Regions 1 and 2, continuous (E) Regions 1, 2, and 3, continuous (F) Regions 1, 2, and 3, separate (G) Regions 1 and 2, continuous, but separate from 3 (H) Regions 2 and 3, separate (I) Regions 2 and 3, continuous, but separate from 1 (J) Region 3 alone (K) Region 3 and 4, continuous (may include calcification in one other region) (L) No styloid process visible. Results: The right SPs were found to be longer than the left (p<0.05). Types D (right 42.9%, left 42%) and E (right 33.3%, left 30.8%) were the most common morphological calcifications on both sides. No statistical difference was found for bilateral SP length between gender, age, and dental status groups. A significant difference was found only for right SP morphological calcification types as to age groups in both genders (p<0.05). No significant difference was found for SP morphological calcification types according to gender and dental status. Conclusion: The morphological types are formed at their present area. Even though SP calcification type was determined according to the length of SP, age was not an effective factor on the length, but the morphological calcification type of SP. Therefore, factors other than age may have a role in the development of morphological calcification types. Structural characteristics of SP are not associated with age, gender and dental status.